PERAN PEMERINTAH DAERAH DALAM DALAM KONTEKS EKSPRESI BUDAYA TRADISIONAL DALAM PERLINDUNGAN HAK CIPTA (Studi terhadap Peraturan Daerah Provinsi Jawa Barat Nomor 10 Tahun 2018) - Takarada, Yudi (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
Whereas the regulation on Intellectual Property Rights law has been universally applied and accepted by the members of the World Trade Organization (WTO) by making separate rules into the positive law of each WTO member country. The existence of West Java Provincial Regulation Number 10 of 2018 concerning Intellectual Property Management including Traditional Cultural Expressions in it, can mean that the said Regulation acts as a "private legal entity" which can lead to confusion over higher laws and regulations or known as lex superiori derogat legi inferiori (higher regulations override lower regulations), in that context in Indonesia there have been various laws governing Intellectual Property law, namely: Law on Plant Variety Protection, Law on Industrial Design, Law on Layout of Integrated Circuits, Law on Trade Secrets, Law on Copyright, Law on Patents and Law on Marks and Geographical Indications. The Regional Regulation Number 10 of 2018 has the potential to abuse authority and can be categorized as a problematic regional regulation that can lead to confusion in the community.